Biochemical Evidence for a Putative Inositol 1, 3, 4, 5-Tetrakisphosphate Receptor in the Olfactory System of Atlantic Salmon (Salmo salar). (11th March 2013) - Pang, Jiongdong; Rhoads, Dennis E.
Abstract : Olfactory receptor neurons in Atlantic salmon ( Salmo salar ) appear to use a phosphoinositide-directed phospholipase C (PLC) in odorant signal transduction. The consequences of odor-activated PLC depend on its product, inositol 1, 4, 5-trisphosphate (IP3 ). Therefore, a plasma membrane rich (PMR) fraction, previously characterized from salmon olfactory rosettes, was used to study binding sites for IP3 and its phosphorylation product, inositol 1, 3, 4, 5-tetrakisphosphate (IP4 ). Binding sites for IP3 were present at the lower limit for detection in the PMR fraction but were abundant in a microsomal fraction. Binding sites for IP4 were abundant in the PMR fraction and thus colocalized in the same subcellular fraction with odorant receptors for amino acids and bile acids. Binding of IP4 was saturable and high affinity (K d  = 83 nM). The rank order for potency of inhibition of IP4 by other inositol polyphosphates (InsP x ) followed the phosphorylation number with InsP6 > InsP5 > other InsP4 isomers > InsP3 isomers > InsP2 isomers, with the latter showing no activity. The consequences of PLC activity in this system may be dictated in part by a putative receptor for IP4 .